9-Mercaptodethiobiotin is Formed as a Competent Catalytic Intermediate by Escherichia coli Biotin Synthase - Taylor, Andrew M. (2008)
Biotin synthase (BS) catalyzes the oxidative addition of a sulfur atom to dethiobiotin (DTB) to generate the biotin thiophane ring. This enzyme is an S-adenosylmethionine (AdoMet) radical enzyme that catalyzes the reductive cleavage of AdoMet, generating methionine and a transient 5´-deoxyadenosyl radical. In our working mechanism, the 5´-deoxyadenosyl radical oxidizes DTB by abstracting a hydrogen from C6 or C9, generating a dethiobiotinyl carbon radical that is quenched by sulfide from a [2Fe-2S](2+) cluster. A similar reaction sequence directed at the other position generates the second C-S bond in the thiophane ring. Since the BS active site holds only one AdoMet and one DTB, it follows that dissociation of methionine and 5´-deoxyadenosine and binding of a second equivalent of AdoMet must be intermediate steps in the formation of biotin. During these dissociation/association steps, a discrete DTB-derived intermediate must remain bound to the enzyme. In the present work, we confirm that the conversion of DTB to biotin is accompanied by the reductive cleavage of 2 equivalents of AdoMet. A discrepancy between DTB consumption and biotin formation suggests the presence of an intermediate, and we use LCMS to demonstrate that this intermediate is indeed 9-mercaptodethiobiotin, generated at ~10% of the total enzyme concentration. The amount of intermediate observed is increased when the reaction is run with substoichiometric levels of AdoMet or with defective enzyme containing the mutation Asn153Ser. The retention of 9-mercaptodethiobiotin as a tightly-bound intermediate is consistent with a mechanism involving the stepwise radical-mediated oxidative abstraction of sulfide from an iron-sulfur cluster.